Listening Strategies used by Mono- and Bilingual Majors of English at the F. Rákóczi II Transcarpathian Hungarian Institute - Fábián Márta; Фабіян Марта („RIK-U” Kft., 2018)
Abstract. Teaching listening skills is one of the most difficult tasks for EFL teachers as successful listening skills are acquired over time and with lots of practice. One of the largest inhibitors for students is the mental block. Listening strategies are techniques and activities that contribute directly to the comprehension and recall of listening input. The study aims to get insight into the EFL listening strategy use of the learners majoring in English and compare the non-interactive or unidirectional listening strategy use of bilingual and monolingual learners with the help of a standardised questionnaire called ELLSI. The results show a wide variety of strategy use. The highest ranks have the groups of cognitive strategies followed by metacognitive ones while the socio-affective strategies proved to be the less frequently used group. The strategy use of bilingual learners proved to be different from their monolingual peers. Bilingual learners use more strategies than monolingual ones. Altogether seven strategies are more frequently used by the bilingual group than the monolingual one from which four belong to cognitive strategies, three to socio-affective and one was a metacognitive strategy. In processing the information bilingual learners use top-down strategies, they rely more on their background knowledge, more often use clarification strategies and strategies for reducing anxiety. Besides, they are more cooperative with their peers.
https://opac3.brff.monguz.hu:443/hu/record/-/record/bibBRF00006453
Keywords: Listening Strategies; Mono- and Bilingual Majors of English; Ferenc Rákóczi II Transcarpathian Hungarian Institute